Термогазохимическое воздействие на малодебитные и осложненные скважины - Чазов Г. А. Геннадий Александрович; Азаматов В. И. Венер Идиатуллович; Якимов С. В. Сергей Владимирович; Савич А. И. Александр Ильич (Москва, Недра, 1986)
Авт. указаны на обороте тит. л.